Inventory System Development With Trend Moment Method For Optimization Warehouse Inventory Using Rfid Technology ( Case Study At Pt. Jansen Indonesia) - Muhammad Fathony; Good Sudirman (Journal of Technology Informatics and Engineering, 2023)
Abstract - In warehouse department or warehouse in the company including PT. Jansen Indonesia has system service still available Not yet maximizing development technology moment this is the medium one develop fast . Including in system inventory Frequent warehouse​ happen No make it available stock And Excessive stock .​ This matter cause function inventory on warehouse No Work in a way maximum. From problem said , PT. Jansen Indonesia requires exists optimization stock with use Trent Moment Method with web- based and use RFID technology . System This covers control supply on warehouse For purchase so that reduce stock excessive nor less so supplies stock controlled , as well as a data input process that utilizes RFID so that speed up time in the data input process. On system This use Language PHP and MYSQL programming as databases as well utilizing the PHP Framework , namely Codeigniter in creation of this website . With exists system web based , makes it easy employee in data processing with appropriate time .